Análise discursiva dos Ethé de um sujeito político em campanha eleitoral - Mesti, Paula Camila (2010)
The predominance of the image, the speed of information transmission, the super valorization of the media, the metamorphosis occurred in how to make policy, the impossibility of separating the word from the body which enunciates are unexceptional practices in the current globalised world. Considering this context, the changes in contemporary political discourse and the theoretical device of Discourse Analysis, this research is addressed to the construction of images that the political subject Silvio Barros gives about himself in his speeches for mayor of Maringá-PR. The corpus of analysis of this research is consisted of the recordingsand transcriptions of Free Timetables of Electoral Advertising on television (HGPE) of the marketing years of 2004 and 2008. Its verification enabled some concerns: what makes it possible to define what types of ethé shall be constructed in each election campaign? To analyze the ethé a political subject, it must be to only consider its discourse? Is there a technical know-how that contributes to the strengthening of these ethé? Based on these questions some objectives are mapped out: in general, it was contributed to the enlargement of the concept of discursive ethos for, more specifically, to define and to establish the construction of ethé of the political subject Silvio Barros. In order to produce gestures of interpretation, different discursive materialities were used: transcriptions of verbal texts, jingles, tables, discursive sequencies, infographic, picture frames. These are the materialities that guide the research to multiple methodological paths that converge to the obtaining of interesting results: a) the existence of overlapping types of ethé; b) the simultaneity of positive ethé construction for the candidate and negative ethé for his opponent, and c) the appeal to sporting and religious discursive formations in order to avoid the drift of the meaning effects produced by the ethé. It is also important to highlight the speech importance of the witness subjects, the presence of audiovisual and the use of technical know-how that contribute to the edification of the credibility and of the process of the elector / viewer identification with the political subject.